2018
DOI: 10.1002/isd2.12064
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for m‐Government adoption in Tanzania: A conceptual framework

Abstract: The advancement of wireless and mobile technologies has given rise to the mobile government (m-Government). A new channel of public service delivery using a mobile phone. In Tanzania, several m-Government initiatives have been undertaken. Among these, some can be said to have succeeded while others are still struggling. The reasons for these variations are not known. This study aimed to capture the critical success factors (CSFs) for the adoption of m-Government and propose a framework under the Tanzanian cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…Mobil Hizmet Kabul Modeli'ne göre de yararlılık, kullanım kolaylığı ve güven mobil hizmeti kullanma niyetini direk etkilemektedir (Gao, Krogstie & Gransaether, 2008). Bir diğer çalışma sonucunda da bu üç faktöre ilaveten erişim, altyapı ve kullanılabilirlik de m-devlet kullanmayı etkileyen faktörler olarak rapor edilmiştir (Ishengoma et al, 2019). Farklı ülkelerde yapılan araştırma sonuçlarının büyük çoğunluğunda da bu üç faktörün etkili olduğu Tablo 1'de görülmektedir.…”
Section: Sonuç Ve öNeri̇lerunclassified
See 2 more Smart Citations
“…Mobil Hizmet Kabul Modeli'ne göre de yararlılık, kullanım kolaylığı ve güven mobil hizmeti kullanma niyetini direk etkilemektedir (Gao, Krogstie & Gransaether, 2008). Bir diğer çalışma sonucunda da bu üç faktöre ilaveten erişim, altyapı ve kullanılabilirlik de m-devlet kullanmayı etkileyen faktörler olarak rapor edilmiştir (Ishengoma et al, 2019). Farklı ülkelerde yapılan araştırma sonuçlarının büyük çoğunluğunda da bu üç faktörün etkili olduğu Tablo 1'de görülmektedir.…”
Section: Sonuç Ve öNeri̇lerunclassified
“…Bu sonuç değerlendirildiğinde öğrencilerin m-devlet hizmetine erişimi, erişebilecekleri cihazı ve işlem maliyetini kolaylıkla karşılayabildikleri söylenebilir. Literatürde yer alan araştırma sonuçları değerlendirildiğinde bazı çalışma sonuçlarında hizmet maliyetinin m-devlet kullanımını etkilediği görülürken (Al-Hadidi & Rezgui, 2010;Al-khamayseh et al, 2006;Ishengoma et al, 2019) bazıları da etkilemediğini belirtmektedir. (Abu-Shanab & Haider, 2015;El-Kiki & Lawrence, 2006;Hung et al, 2013;Rana et al, 2019).…”
Section: Sonuç Ve öNeri̇lerunclassified
See 1 more Smart Citation
“…A number of theoretical models have been proposed to understand the determinants of technology acceptance and innovation adoption, including the technology acceptance model [23] and its derivatives, the unified theory of acceptance and use of technology (the UTAUT [24] and UTAUT2 [25]). In particular, extensions and adaptations of the TAM and the UTAUT models have been applied to predict and explain the adoption of e-government, m-government, and city apps in particular (for example, [11,[26][27][28][29][30][31][32][33]). Across these studies (see also [27] for a review), several factors have been consistently examined and found to be predictive of adoption or intention to adopt smart city applications and/or m-government: Perceived usefulness of the technology (termed performance expectancy in more recent models, such as UTAUT [25]), perceived ease of use of the technology (termed effort expectancy in more recent models), costs (reconceptualized as price-value in more recent models), social influence (perceived expectations of others in one's social environment), privacy concerns, and trust in the government and/or provider of the technology.…”
Section: Understanding Adoption Of City Apps Through Technology Accepmentioning
confidence: 99%
“…For example, potential users might perceive a "cost" associated with installing and using city service apps, which can take up valuable mobile storage space [12]. Additionally, recent investigations of technology and m-government adoption have consistently identified concerns about invasion of privacy and personal safety (e.g., [8,27,54,55]). Such "cost" concerns can influence citizens' evaluation of the apps.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%